A Cranio-Facial Dysmorphic Foetus; A New Syndrome? - Prasanna, LC (Journal of Nepal Paediatric Society, 2013)
Cranial Neural Crest (CNC) cells interact with and are consequently instructed by the pharyngeal endoderm, the branchial arch ectoderm, and the isthmic organizer at the midbrain– hindbrain boundary before giving rise to various types of tissues such as bone, cartilage, tooth, and cranial nerve ganglia in the craniofacial region. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7672 J Nepal Paediatr Soc. 2013; 33(2):155-156